Rapidly intensified beef production in Uruguay: Impacts on water-related ecosystem services - Ran, Ylva; Deutsch, L.; Lannerstad, Mats; Heinke, J. (Elsevier, 2013)
Livestock production is one of the fastest growing agricultural subsector globally. Expansion and intensification of animal production increase demand for natural resources. Sustainable intensification approaches are needed that limit pressure on often already scarce land and water resources. This paper quantifies water requirements in three Uruguayan beef production systems - extensive, mixed and intensive - and explores impacts on water-related ecosystem services. Mixed beef production systems were found to make most effective use of water. However, the shift from pastures in crop rotation towards continuous feed-crop cultivation decreases soil organic-matter contents, reducing soil water-holding capacity; this may result in lower agricultural yields and reduced resilience to droughts.